Syndrom krátké klicky - Rath, D; Keil, R; Vecer, J (Vnitrni lekarstvi, 2000)
The authors demonstrate on case-histories their experience with short-loop syndrome which develops after extensive resections of the small intestine. The clinical picture of the syndrome is characterized by diarrhoea, steatorrhoea, maldigestion and malabsorption with loss of body weight. Non-surgical treatment of the syndrome copies its different stages. The objective of conservative therapy is above all to preserve the nutritional integrity of the organism and gradual adaptation of the gut which will make eventually a change to oral intake possible. This adaptation takes 1 to 2 years. Last not least, treatment should eliminate the diarrhoea. The authors demonstrate on examples that properly conducted treatment prevented the development of malnutrition, contrary to another case where the sequelae of surgery were underestimated and the patient developed cachexia and pernicious anaemia.
Keywords: Short Bowel Syndrome; lidé; syndrom krátkého střeva; Adult; Male; dospělí; Humans; mužské pohlaví